Intense pulsed light is effective in treating postburn hyperpigmentation and telangiectasia in Chinese patients. (17th November 2018) - Li, Na; Han, Juntao; Hu, Dahai; Cheng, Jing; Wang, Hongtao; Wang, Yunchuan; Yang, Xuekang; Liu, Jiaqi; Li, Ting; Zhao, Wenli
ABSTRACT: Intense pulsed light (IPL) has been used to treat postinflammatory hyperpigmentation and telangiectasia in Fitzpatrick type I -II skin. However, its therapeutic effects after superficial second-degree burns in Asian populations with Fitzpatrick type III-IV skin are uncertain. Thirty-five Han Chinese patients with facial or hand hyperpigmentation and telangiectasia due to second-degree fire burns received treatment with IPL. Each patient underwent 2–6 treatments over 3–5 weeks. The laser wavelength was 560–615 nm. Skin pigmentation was evaluated by two plastic surgeons as well as by the patients themselves (self-evaluation) before treatment at the end of the treatment cycle and 1 year after the first treatment. Blood flow in telangiectasia skin was measured by laser Doppler flow. The results showed that IPL significantly lessened hyperpigmentation so that close to normal skin color was achieved after the treatment cycles, and pigmentation did not reoccur 1 year after the first treatment. Approximately 82.9% of the patients were satisfied with their treatment outcomes. There were no post-treatment complications. Doppler showed a significant decreased blood flow in telangiectasia after treatment. In conclusion, IPL is an effective and safe modality for Chinese patients with hyperpigmentation and telangiectasia after fire burns.